Chapter 22 - Investigating cell-type specific functions of tenascin-C - Murdamoothoo, D; Schwenzer, A; Kant, J; Rupp, T; Marzeda, A; Midwood, K; Orend, G (Elsevier, 2017)
The extracellular matrix molecule tenascin-C (TNC) has received a lot of attention since its discovery 30 years ago because of its multiple roles in tissue repair, and in pathologies such as chronic inflammation, fibrosis, and cancer. Mouse models with high or no TNC expression have enabled the validation of key roles for TNC in immunity and angiogenesis. In parallel, many approaches including primary cell or organ cultures have shed light on the cellular and molecular mechanisms by which TNC exerts its multiple actions in vivo. Here, we will describe assays that investigate its antiadhesive properties and that measure the effect of TNC on the actin cytoskeleton, cell survival, proliferation, and migration. We will also describe assays to assess the impact of TNC on endothelial and immune cells in cell and organ culture, and to compare the responses of fibroblasts from normal and diseased tissues.